Peningkatkan Minat Belajar Melalui Layanan informasi Pada Siswa SMP - Rusmini Rusmini (Journal Prakarsa Paedagogia, 2018)
The purpose of this study is to know the increase in students' interest in learning through information services provided by counselors. The study was designed with a classroom action research model with a subject of 32 students of class VIII of Cluwak Middle School 1 2017/2018. The results revealed that there was a significant increase between before the study, after the first and second cycles. Researchers suggest that information service innovations continue to be provided to continue to improve the quality of guidance services and counseling, especially information services.